Obesity and associated lifestyles modify the effect of glucose metabolism‐related genetic variants on impaired glucose homeostasis among postmenopausal women. Issue 6 (5th July 2016) - Jung, Su Yon; Sobel, Eric M.; Papp, Jeanette C.; Crandall, Carolyn J.; Fu, Alan N.; Zhang, Zuo‐Feng
ABSTRACT: Purpose: Impaired glucose metabolism‐related genetic variants likely interact with obesity‐modifiable factors in response to glucose intolerance, yet their interconnected pathways have not been fully characterized. Methods: With data from 1, 027 postmenopausal participants of the Genomics and Randomized Trials Network study and 15 single‐nucleotide polymorphisms (SNPs) associated with glucose homeostasis, we assessed whether obesity, physical activity, and high dietary fat intake interact with the SNP–glucose variations. We used regression analysis plus stratification and graphic approaches. Results: Across carriers of the 15 SNPs, fasting levels of glucose, insulin, and homeostatic model assessment‐insulin resistance (HOMA‐IR) were higher in obese, inactive, and high fat‐diet women than in their respective counterparts. Carriers within subgroups differently demonstrated the direction and/or magnitude of the variants' effect on glucose‐relevant traits. Variants in GCKR, GCK, DGKB/TMEM195 ( P for interactions = 0.02, 0.02, and 0.01), especially, showed interactions with obesity: obese, inactive, and high fat‐diet women had greater increases in fasting glucose, insulin, and HOMA‐IR levels. Obese carriers at TCF7L2 variant had greater increases in fasting glucose levels than nonobese carriers ( P for interaction = 0.04), whereas active women had greater decreases in insulin and HOMA‐IR levels than inactive women ( P for interaction = 0.02 in both levels). Conclusions: Our data support the important role of obesity in modifying glucose homeostasis in response to glucose metabolism–relevant variants. These findings may inform research on the role of glucose homeostasis in the etiology of chronic disease and the development of intervention strategies to reduce risk in postmenopausal women.